The Evolvability of Words: On the Nature of Lexical Items in Minimalism - Clark, Brady (Frontiers in Psychology, 2020)
Work within the minimalist program attempts to meet the criterion of evolvability: “any mechanisms and primitives ascribed to UG rather than derived from independent factors must plausibly have emerged in what appears to have been a unique and relatively sudden event on the evolutionary timescale” (Chomsky, Gallego, and Ott 2017). On minimalist assumptions the evolution of the language faculty must have involved at least two major developments: (i) the evolution of a single, simple recursive operation that glues together lexical items and complexes of lexical items and (ii) the evolution of computational atoms, lexical items, understood as bundles of features. The second development, the evolution of lexical items and the lexicon, is especially poorly understood. A complete account of the evolution of lexical items will state what evolved, how, and why. The focus of this article is the first question: what evolved. What properties do lexical items have, what determines these properties, and what is the internal structure of lexical entries? The article identifies what the key open problems are for a minimalist account of the evolution of words that strives to meet the criterion of evolvability.